Pharmacokinetics, Safety, and Tolerability of (R)-Ketamine Hydrochloride Injection, a Novel Rapid-Acting Antidepressant, in Healthy Chinese Subjects - Wang, Rui; Yang, Yuqian; Zhou, Tong; Zou, Bingjie; Ding, Li (Pharmaceuticals (Basel, Switzerland), 2025)
Objectives: (R)-ketamine hydrochloride injection is a novel, rapid-acting antidepressant for the treatment of treatment-resistant depression. The aim of this study was to assess the pharmacokinetics, safety, and tolerability of (R)-ketamine hydrochloride injection in healthy Chinese subjects following ascending single intravenous doses ranging from 10.0 mg to 180 mg. Methods: This randomized, double-blind, placebo-controlled study was conducted in 50 healthy male and female Chinese subjects after single ascending doses of (R)-ketamine hydrochloride injection (10.0, 30.0, 60.0, 120, and 180 mg). Ten subjects (including two subjects treated with a placebo) were included in each dose cohort. Pharmacokinetic characteristics, safety, and tolerability profiles of the study drug were evaluated. Results: After the intravenous doses administered from 10.0 mg to 180 mg of (R)-ketamine hydrochloride injection to the subjects, the Cmax and AUC values for both (R)-ketamine and its metabolite (R)-norketamine in the subjects increased approximately proportionally to the doses. The average peak plasma concentration levels at the five dose cohorts ranged from 56.0 to 1424 ng/mL and 27.7 to 491 ng/mL for (R)-ketamine and (R)-norketamine, respectively. The adverse events of (R)-ketamine hydrochloride injection were temporary and recovered spontaneously without treatment. Conclusions: In summary, (R)-ketamine hydrochloride injection was safe and well tolerated in healthy Chinese subjects. The clinical study results laid a foundation for the further clinical studies of (R)-ketamine hydrochloride injection in patients.